Factors related to drug consumption among Mexican prisoners - Juárez García, Laura Rocío (2020)
Hyperactivity in the Behavioral Approach System (BAS) and hypoactivity in the Behavioral Inhibition System (BIS) are related to substance use and antisocial personality disorders, andan inherent variable is impulsivity. Objective: To determine the association between BIS / BAS systems, impulsivity and types of crime, with drug consumption. Method: quantitative crosssectional and correlational research. Sample: 175 Persons Deprived of Liberty. Instruments: BIS / BAS Plutchik Impulsivity Scale and a specific questionnaire was developed to evaluate sociodemographic variables. A significant correlation was found between drug use, crime (p .002) and impulsivity (p <.001), as well as other prison variables linked to consumption. No association was found between BIS / BAS systems and drug consumption.